PEMBIAKAN ZAMIO MENGGUNAKAN SETEK DAUN PADA BERBAGAI MEDIA, TARAF CAHAYA, DAN KONSENTRASI IBA - Sugijono, Sugijono; Sumijati, Sumijati (Caraka Tani: Journal of Sustainable Agriculture, 2009)
Ornamental plant mainly indoor kind like zamio was isteresting for human. The interesting increase year by year. Easy in maintaining of crop and can be propagated by leaf are more interesting. Crop propagation by leaf will be generate high number of new plants but the plant IBA growth regulation treatment. The research was conducted at open garden of Bussiness Incubator, University of Sebelas Maret Surakarta (98 m above see level) from July untill September 2008. The research contains two experiments there are arrange inn split pot factorial design respectively. For the first experiment the mainplot is light intensity (25, 50 and 75%) and subplot is IBA concentration (0, 100, 200 and 300 ppm). The second experiment the mainplot is light intensity (25, 50 and 75%) and subplot is crop media composition (ash from husk+sand+compost, ash from husk+powder of coconut fiber+compost, and charcoal from husk+powder of coconut fiber+compost). So there are (from the two experiments) 12 combination treatment, each of combination was replicated three times. The yield of research show that: there are no interaction between light intensity and IBA concentration also between light intensity and media composition. The respon of zamio leaf cutting to the light intensity on the number and length of roots following positive lineary model but on the high of bud following negative lineary model especially at 18 weeks after planting (wap). The respon of zamio leaf cutting to the IBA concentration occur at 24 wap following positive lineary model. The media composition no significantly influence to the cutting growth.